2020
DOI: 10.1016/j.chemgeo.2020.119601
|View full text |Cite
|
Sign up to set email alerts
|

Calcium isotopes in deep time: Potential and limitations

Abstract: Calcium is an essential element in the biogeochemical cycles that regulate the long-term climate state of Earth. The removal of CO2 from the ocean-atmosphere system is controlled by the burial of carbonate sediments (CaCO3), ultimately linking the global calcium and carbon cycles.This fundamental link has driven the development of the stable calcium isotope proxy with application to both ancient skeletal and non-skeletal bulk carbonate sediments. Calcium isotope ratios (d 44/40 Ca) have been used to track long… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(17 citation statements)
references
References 183 publications
1
16
0
Order By: Relevance
“…In summary, the combination of the studied sediment mineralogy and early-stage diagenesis with intensive fluid flow in certain settings can account for a significant δ 44/40 Ca range, even in contemporaneous sections. This finding supports the potential of bulk δ 44/40 Ca measurements as a tool to determine diagenetic processes and carbonate mineralogy in environments, where other proxies are lacking or facing difficulties (Gussone et al, 2020).…”
Section: Early Diagenesissupporting
confidence: 79%
See 1 more Smart Citation
“…In summary, the combination of the studied sediment mineralogy and early-stage diagenesis with intensive fluid flow in certain settings can account for a significant δ 44/40 Ca range, even in contemporaneous sections. This finding supports the potential of bulk δ 44/40 Ca measurements as a tool to determine diagenetic processes and carbonate mineralogy in environments, where other proxies are lacking or facing difficulties (Gussone et al, 2020).…”
Section: Early Diagenesissupporting
confidence: 79%
“…On the contrary, in the case of sediment‐buffered conditions, the secondary changes in the δ 44/40 Ca values tend to be far less as a large portion of the Ca is delivered from the sediment itself (Higgins et al., 2018). This early diagenetic effect is arguably most significant at low sedimentation rates, which allows the sediments to remain near to the seafloor for a long time, and can be an important mechanism in platform systems with advective seawater flux (Gussone et al., 2020; Higgins et al., 2018; Lau et al., 2017). Among the investigated sections, Steinbergkogel and Oyuklu present low sedimentation rates.…”
Section: Discussionmentioning
confidence: 99%
“…There is significant interest in using measurements of δ 44/40 Ca in sedimentary carbonations to reconstruct the isotopic and chemical characteristics of the precipitating fluid (Fantle and Tipper, 2014). This requires knowledge of how various aspects of solution chemistry dictate the magnitude of calcium isotope fractionation as well as a broader understanding of the geochemical context in which the minerals were precipitated, including the influence of biomineralization or biologically induced mineralization, closed vs. open-system behavior, and any subsequent recrystallization (Ahm et al, 2018;Higgins et al, 2018;Gussone et al, 2020). Mills et al (2021) demonstrated that Δ 44/40 Ca calcite-fluid is less sensitive to solution stoichiometry than originally predicted, which lends more confidence to interpretations of calcite saturation state and associated growth rate from observed fractionations.…”
Section: Implications For Interpretation Of δ 44/40 Ca In Natural Sys...mentioning
confidence: 99%
“…Over the past years, an increasing number of scholarly studies have compiled data on fluid‐mineral interaction and related re‐equilibration of the carbon isotope geochemistry along burial trajectories and in the metamorphic domain. The isotope systems studied include for example, magnesium (δ 26 Mg and δ 25 Mg; Geske et al, 2015a; Lavoie et al, 2014; Walter et al, 2015; Wang et al, 2015; Young & Galy, 2004); calcium (δ 44/40 Ca; Fantle & Higgins, 2014b; Gussone et al, 2005, 2020; Hu et al, 2019; Higgins et al, 2018; Pokrovsky et al, 2011; Steuber & Buhl, 2006; Tostevin et al, 2019); iron (δ 56 Fe; Frost et al, 2007; Kaufman et al, 1990); molybdenum (δ 98/95 Mo; Voegelin et al, 2010); uranium ( 238 U; Herrmann et al, 2018; Hood et al, 2018); strontium ( 87 Sr/ 86 Sr and δ 88/86 Sr; Banner, 1995; Fantle et al, 2020; Nelson et al, 1986); but also sulphur (δ 34 S CAS ; Fichtner et al, 2017; Mazumdar & Strauss, 2006); among other elements. Given that the isotopes of carbon (δ 13 C) and oxygen (δ 18 O) are still the backbone of many studies focussing on burial carbonates, this chapter focusses these two elements and their stable isotopes.…”
Section: Isotope Geochemistry Of Burial Fluids and Carbonate Cementsmentioning
confidence: 99%